Flavor and Functional Characteristics of Whey Protein Isolates from Different Whey Sources. Issue 4 (22nd February 2016) - Smith, T.J.; Foegeding, E.A.; Drake, M.A.
Abstract: This study evaluated flavor and functional characteristics of whey protein isolates (WPIs) from Cheddar, Mozzarella, Cottage cheese, and rennet casein whey. WPIs were manufactured in triplicate. Powders were rehydrated and evaluated in duplicate by descriptive sensory analysis. Volatile compounds were extracted by solid‐phase microextraction followed by gas chromatography‐mass spectrometry. Functional properties were evaluated by measurement of foam stability, heat stability, and protein solubility. WPI from Cheddar and Cottage cheese whey had the highest cardboard flavor, whereas sweet aromatic flavor was highest in Mozzarella WPI, and rennet casein WPI had the lowest overall flavor and aroma. Distinct sour taste and brothy/potato flavor were also noted in WPI from Cottage cheese whey. Consistent with sensory results, aldehyde concentrations were also highest in Cheddar and Cottage cheese WPI. Overrun, yield stress, and foam stability were not different ( P > 0.05) among Cheddar, Mozzarella, and rennet casein WPI, but WPI foams from Cottage cheese whey had a lower overrun and air‐phase fraction ( P < 0.05). Cottage cheese WPI was more heat stable at pH 7 ( P < 0.05) than other WPI in 4% protein solutions, and was the only WPI to not gel at 10% protein. Cottage cheese WPI was less soluble at pH 4.6 compared to other WPI ( P < 0.05) and also exhibited higher turbidity loss at pH 3 to 7 compared to other WPI ( P < 0.05). This study suggests that WPI produced from nontraditional whey sources could be used in new applications due to distinct functional and flavor characteristics.